PEMANFAATAN SMART TV SEBAGAI MEDIA PEMBELAJARAN DIGITAL ADAPTIF UNTUK MENINGKATKAN INTERAKSI DAN KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR - MUTIARA FAUZIAH; NAILATUL FADHILA; ADRIAS ADRIAS; NUR AZMI ALWI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of educational technology has encouraged elementary schools to utilize more interactive and adaptive digital learning media, one of which is through the use of Smart TVs. This study aims to analyze the utilization of Smart TVs as digital learning media to improve interaction and independent learning among elementary school students. The research employed a literature review method with a qualitative approach. Data were collected through a review of various national scientific articles published between 2021–2026 from Google Scholar, Garuda, and accredited national journals. This study refers to 10 scientific journals discussing the utilization of Smart TV-based digital learning media and interactive technology in elementary school learning as the foundation for the research analysis.. The results of the review indicate that Smart TVs are capable of creating a more engaging learning process through videos, animations, interactive quizzes, and educational games that can enhance students’ attention, motivation, and participation during the learning process. In addition, Smart TVs support adaptive learning because teachers can adjust the learning materials according to students’ needs and learning abilities. The use of digital applications such as Wordwall, Liveworksheet, and Google Slides also helps create an active, innovative, and enjoyable learning environment, enabling students to become more independent in understanding the material. Based on various previous studies, the use of Smart TVs has a positive impact on the quality of learning in elementary schools, especially in building two-way communication between teachers and students. However, its implementation still faces several challenges, such as limited internet access, inadequate school facilities, and the need to improve teachers’ digital competencies. Therefore, training and technological facility development are needed to ensure that the utilization of Smart TVs can be implemented optimally and sustainably.